MENINGKATKAN PEMAHAMAN HADIS AL-ṢIDQ MASYARAKAT DESA LERPAK LANTONG MELALUI MAJELIS MUSLIMATAN - Farhah, Sailatul; Mufida, Inatul; A'yun, Qurrotu; Sadiyah, Fatichatus (Karsa Bhakti : Journal of Community Service, 2026)
This community service activity was motivated by the low level of public moral awareness regarding the significance of honest behavior (al-Ṣidq) and the negative impact of lying (kaẓẓāb). The main objective of this intervention is to revitalize social conditions that tend to be permissive of dishonest behavior, especially in  horizontal interactions between neighbors, which often trigger disharmony. Women were designated as the primary target audience, given that observations indicated that this group was often involved in dishonest practices, particularly in the context of communal conversations (gossip). This community service method combines socialization and participatory discussions, which are carried out in three stages: 1) Initial Needs Analysis of the sociocultural conditions of the Lerpak Village community. 2) Dissemination of Core Material in the form of hadiths about the recommendation of al-Ṣidq and the prohibition of (kaẓẓāb). And 3) Active Interactive Discussion between the implementation team and participants. The result of this activity was an increase in the community's understanding of honesty (al-Ṣidq), which was emphasized as an essential foundation for maintaining harmonious neighborly relations and strengthening ukhuwah islamiyah (Islamic brotherhood).